If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2x = 4x + -7 Combine like terms: 3x + 2x = 5x 5x = 4x + -7 Reorder the terms: 5x = -7 + 4x Solving 5x = -7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5x + -4x = -7 + 4x + -4x Combine like terms: 5x + -4x = 1x 1x = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 1x = -7 + 0 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| f=8+3f | | 95-3x=24x+23 | | 6x+12x-9-8x+10+x=0 | | 3x-5/9+x=3x+5/3+5 | | x-3+6x-9+12x-15=x | | -3-9x=8x+21 | | .12x+.6(x-4)=.01(3x-1) | | 15x+120=x | | 8y+6y=56 | | (29/36)x+120=x | | 60x-13=72x-3-24x | | 103-2x=16x+21 | | 5x-15+2x-14=x-11 | | 5x-2x+12=35-4x-9 | | y=-(1+1)(1-3) | | 2g-8=10-4g | | X^2+7-9=0 | | 105*13/35*8/9 | | 5x-3.2=2x+2.8 | | 7x-91=2x-6 | | 32=17+x/2 | | 9x+10=3x+40 | | 48-2x=16x+24 | | F-2=3f+6 | | 5(x+3)+3(x-1)=-9 | | X/4+7=14 | | 21=(5x/6)+(3x/2) | | 2(x-4)+3(x+5)=2x | | 5.3q-1.9-4.6q=-0.3q-1.5 | | 2x-8+3x+18=2x | | 33/25*10/117*27/22 | | -2y+5x=-9 |